Quantitative measurement of complex substances dissolved in an ionic liquid using IR spectroscopy and chemometrics - Kiefer, Johannes; Bösmann, Andreas; Wasserscheid, Peter (Technisches Messen, 2017)
In the past two decades, ionic liquids have found many applications as solvents for complex solutes. Prominent examples are the dissolution of biomass and carbohydrates as well as catalytically active substances. The chemical analysis of such solutions, however, is still a challenge due to the molecular complexity. In the present work, the use of infrared spectroscopy for quantifying the concentration of different solutes dissolved in an imidazolium-based ionic liquid is investigated. Binary solutions of glucose, cellubiose, and Wilkinson's catalyst in 1-ethyl-3-methylimidazolium acetate are studied as examples. For this purpose, different chemometric approaches (principal component analysis (PCA), partial least-squares regression (PLSR), and principal component regression (PCR)) for analyzing the spectra are tested. Principal component analysis was found to be suitable for classifying the different solutions. Both regression techniques were capable of deriving accurate concentration values. The performance of PLSR was slightly better than that of PCR for the same number of components.
CRIS-Team Scopus Importer:2023-03-29
Keywords: FTIR; Hauptkomponentenanalyse; Konzentrationsbestimmung; Regression